Evaluation of the Implementation of Electronic Medical Records (EMR) in SIMRS Morbis at Hospital X Using HOT-Fit Method - Sali Setiatin; Hanadia Maheswari (Greenation Publisher & Yayasan Global Research National, 2025)
Evaluation of the implementation of Electronic Medical Records (EMDR) in the Hospital Management Information System (SIMRS) is crucial to ensure the effectiveness of health services. This study examines the implementation of EMR in SIMRS MORBIS at Hospital X. The purpose of the study was to evaluate the success of the implementation using the HOT-Fit model by analyzing the Human, Organizational, Technology, and Net Benefit aspects. The research method used a quantitative approach by distributing HOT-Fit -based questionnaires to SIMRS MORBIS users, and the data was analyzed descriptively. The results showed a successful implementation of the human component (average score of 3.95) showing high adoption and satisfaction, the organizational component (3.85) was supportive but internal communication needed to be improved, the technology component (3.58) had good information quality, but system quality needed attention and significant Net Benefit (3.83-3.91) was achieved in efficiency and service quality. It was concluded that the implementation of EMR in SIMRS MORBIS at Hospital X was generally successful and had a positive impact, but optimization of the system quality and internal communication of the organization was needed to improve overall performance.